Neural Correlates of Anhedonia in Major Depressive Disorder: Insights from Concurrent Analysis of Feedback-Related Negativity and Stimulus-Preceding Negativity - Sun Y; Huang Z; Gao X; Chen L; Wang J; Zhou Z; Zhou H (Neuropsychiatric Disease and Treatment, 2023)
Yifan Sun,1 Zixuan Huang,2 Xuezheng Gao,1 Limin Chen,3 Jun Wang,1,3 Zhenhe Zhou,1,3 Hongliang Zhou4 1Department of Psychiatry, The Affiliated Wuxi Mental Health Center of Nanjing Medical University, Wuxi City, 214151, People’s Republic of China; 2Department of Music and Wellbeing, School of Music, University of Leeds, Leeds City, UK; 3Department of Psychiatry, The Affiliated Mental Health Center of Jiangnan University, Wuxi City, 214151, People’s Republic of China; 4Department of Psychology, The Affiliated Hospital of Jiangnan University, Wuxi City, 214151, People’s Republic of ChinaCorrespondence: Jun Wang, Department of Clinical Psychology, The Affiliated Wuxi Mental Health Center of Nanjing Medical University, Wuxi City, 214151, People’s Republic of China, Tel +86 13358119628, Fax +86 51083219366, Email woodfish2@126.com; Zhenhe Zhou, Department of Psychiatry, The Affiliated Wuxi Mental Health Center of Nanjing Medical University, Wuxi City, 214151, People’s Republic of China, Tel +86 13358118986, Fax +86 51083219366, Email zhouzh@njmu.edu.cnPurpose: Anhedonia, a core symptom of major depressive disorder (MDD), is explored in this study, focusing on the neural underpinnings through the examination of two event-related potential (ERP) components: feedback-related negativity (FRN) and stimulus-preceding negativity (SPN).Patients and Methods: This cross-sectional study was conducted in China from March 2022 to March 2023. It involved 35 MDD patients and 31 healthy controls (HC) participating in a modified 2-door task with simultaneous EEG recordings. Depression severity and anhedonia were assessed using the Hamilton Depression Scale (HAMD) and the Temporal Experience of Pleasure Scale (TEPS-CV), respectively. FRN and SPN metrics, along with correlations with each other and clinical assessments, were examined.Results: In comparison to the HC group, the MDD group exhibited significantly lower scores in TEPS-CV (t = 2.854, p = 0.006) and its subscales (t = − 3.596, p = 0.001 and t = 2.434, p = 0.018, respectively), along with consistently reduced amplitudes of FRN (F 1.64= 4.726, p = 0.033) and SPN (F 1.64= 4.195, p = 0.045) across all conditions. Limited correlations were observed between ERP metrics and clinical indicators, except for positive correlations between FRN amplitudes (loss minus win) and HAMD scores (r = 0.392, p = 0.020), and SPN amplitudes after losing (SPN-L) and TEPS-CV consumption subscale scores (r = 0.357, p = 0.035). Notably, while the HC group displayed no significant FRN-SPN correlations, the MDD group exhibited positive FRN-SPN correlations under distinct conditions (r = 0.376, p = 0.026 and r = 0.355, p = 0.037, respectively).Conclusion: Our data reveal subjective and objective anhedonia in both consumption and anticipation, suggesting a shared impairment in reward feedback processing and anticipatory neural mechanisms in individuals with MDD. These findings deepen our understanding of anhedonia’s neural foundations and may guide targeted interventions for this core symptom.Keywords: major depressive disorder, anhedonia, event-related potential, reward processing, feedback-related negativity, stimulus-preceding negativity